Latent heat thermal energy storage in a shell-tube design: Impact of metal foam inserts in the heat transfer fluid side - Ghalambaz, Mehdi; Sheremet, Mikhail A.; Raizah, Zehba; Akkurt, Nevzat; Ghalambaz, Mohammad (Journal of energy storage)
The improvement of heat transfer in latent heat thermal energy storage (LHTES) system is a crucial task. In the current study, the impact of diverse metal foam (MF) layer arrangements on heat transfer fluid (HTF) within a shell-tube LHTES is explored. Six distinct cases (A-F) with varied MF coverage percentages and layer dimensions were assessed. The local thermal non-equilibrium model was utilized to take into account the PCM and MF temperatures. The finite element method was used for solving the partial differential equations. The impact of MF configurations and inlet pressures (250 Pa, 500 Pa, and 750 Pa) on the thermal energy storage/release was addressed. Cases A-C, featuring a 50 % MF concentration, exhibit shorter melting times than Cases Dsingle bondF, with decreasing MF concentrations. A higher MF concentration improves the melting process due to increased thermal conductivity and lower thermal resistance on the HTF side. Cases Dsingle bondF, with a centralized MF layer and decreasing concentrations from 25 % to 6.25 %, display progressively shorter melting times, suggesting that a lower MF concentration leads to more efficient melting. Solidification times also decrease with increasing inlet pressures across all cases. Reynolds numbers, influenced by average HTF tube outlet velocity, vary substantially across cases and inlet pressure differences. Cases A-C demonstrate similar Reynolds numbers for each inlet pressure difference, while Cases Dsingle bondF show a more pronounced increase in Reynolds numbers as the MF layer is reduced and flow resistance drops. Cases A (50 % MF layer) and F (6.5 % MF layer) provide the quickest charging and discharging times due to their unique combination of MF layer properties and inlet pressures. The study highlights the need to consider MF layer composition and inlet pressure when designing optimal LHTES systems for efficient energy storage/release.